El "concierto sacro" del 19 de abril de 1810: 0 la conjura eclesiástica de Andrés Bello (1781-1865) The "Sacred Contriving" of April 19th, 1810: or the Ecclesiastical Conspiracy of Andrés Bello (1781-1865) - David Coifman Michailos (Revista Musical Chilena, 2012)
El concierto sacro delJueves Santo, 19 de abril de 1810, marcó el inicio del movimiento independentista de Venezuela. La fecha no fue escogida al azar, sino que a propósito de las ventajas que la "función eclesiástica" de ese día proporcionaba para el control social y la difusión de la información en torno a los hechos políticos que se buscaba alcanzar. El presente ensayo se propone examinar la confluencia musical y eclesiástica (hasta ahora no estudiada) que habría sin duda sido necesaria establecer para el positivo resultado de esta empresa, supeditada a las redes sociales, musicales e intelectuales en torno al editor entonces de la Gazeta de Caracas, hijo del músico y abogado Bartolomé Bello (1758-1804), el humanista Andrés Bello (1781-1865). The sacred contriving on Maundy Thursday, April 19th, 1810, marked the beginning of the independence of Venezuela. The date was not chosen at random but on the basis ofthe advantages that the "ecclesiasticalfunction" had regarding both the social control and the dissemination ofthe information about the political goals to be achieved. The purpose ofthis essay is the analysis ofthe hitherto unknown confluence ofthe musical and ecclesiastical elements that made it possible this enterprise to succeed. These elements in turn are related to the social, intellectual and musical networks ofthe humanist Andrés Bello (1781-1865), editor ofthe Gazeta de Caracas and son ofthe musician and lawyer Bartolomé Bello (1758-1804).